Kewarisan Anak dalam Kandungan, Anak Zina dan Anak Li’an - Darmawan Darmawan (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Abstract: The child in the womb will receive inheritance, if (1) the child is born alive, and (2) the child is already in the womb of his mother when the muwarrith is died. The child who's born of adultery (zina) is only have a relationship with his mother, in nasab and inheritance. The child of li'an is the child whos's born from teh woman who have been accaused for committing adultery (zina) by her husband , so that child who is born also have the same status as the childr of zina. The accusation was held in a situation of swear to one another between the husband and his wife (the mother of the child of li'an) which caused damage to the husband-wife relationship, so that it was forbidden to reconcile (rujuk) or marry for ever. The child of li'an only has a relationship with the mother who gave birth to him, while the nasab relationship with his father has been demage, so is his inheritance